2022
DOI: 10.1029/2021jc018144
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Wave Height Distributions and Characteristic Wave Periods in Coastal Environments

Abstract: The short‐term statistics of wave conditions in coastal waters around the United Kingdom have been investigated using over 40,000 half‐hour long sea state records with significant wave height greater than 3 m. The extensive data set facilitates an assessment of various wave height and period distribution models in shallow and intermediate waters. The results reveal that the relative wave height Hs/D (where Hs is the significant wave height and D the water depth) can serve as a key indicator in choosing the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Ref. [83] showed that deep-water wave height distribution models perform best with relative wave heights H r < 0.2 m. All three ROIs meet this threshold with mean water depths greater than 20 m and relative wave heights H r between 0.03 m and 0.05 m (Table 6). The opposite is true for Catton Point with ROI 7.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Ref. [83] showed that deep-water wave height distribution models perform best with relative wave heights H r < 0.2 m. All three ROIs meet this threshold with mean water depths greater than 20 m and relative wave heights H r between 0.03 m and 0.05 m (Table 6). The opposite is true for Catton Point with ROI 7.…”
Section: Discussionmentioning
confidence: 92%
“…Based on the rank-sum test method, no significant differences occur between ROI 6 and ROIs 2 and 3 throughout the dataset. The distribution of the wave heights is similar and can be considered as deep-water wave heights according to [83]. Ref.…”
Section: Discussionmentioning
confidence: 99%